Effect of Profitability, Earnings Per Share, and Firm Size on Stock Prices with Corporate Governance Moderation - Derra Ananda Waluyo; Suwitho (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2026)
Objective – To examine and analyze the effects of profitability, earnings per share, and firm size on stock prices, and to determine the moderating role of good corporate governance in processed food subsector companies listed on the Indonesia Stock Exchange during 2020-2024. Design/Methodology/Approach – This study employs a quantitative approach using secondary data from 10 companies, resulting in a total of 50 observations. Profitability is measured by return on assets, EPS by net income per shares outstanding, firm size by the natural logarithm of total assets, stock price by closing price, and GCG by institutional ownership. The analysis method used is Moderated Regression Analysis (MRA) with SPSS 26. Findings – The results show that profitability, EPS, and firm size have a positive and significant effect on stock prices. GCG does not moderate the relationship between profitability and stock prices but significantly moderates the effects of EPS and firm size. Implications – Financial performance variables are key determinants of stock prices, while GCG enhances investor confidence, particularly in earnings and firm scale, offering theoretical support and practical guidance for companies and investors.